2022
DOI: 10.1080/23144599.2022.2139985
|View full text |Cite
|
Sign up to set email alerts
|

A study of viral pathogens in bat species in the Iberian Peninsula: identification of new coronavirus genetic variants

Abstract: Bats have long been associated with multiple pathogens, including viruses affecting humans such as henipaviruses, filoviruses, bunyaviruses and coronaviruses. The alpha and beta coronaviruses genera can infect most mammalian species. Among them, betacoronavirus SARS-CoV, MERS-CoV and SARS-CoV-2, which have caused the three major pandemics in the last two decades, have been proposed to originate in bats. In this study, 194 oral swabs from 22 bats species sampled in 19 locations of the Iberian Peninsula were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…The availability of a highly sensitive and specific diagnostic assay is indispensable for the identification of cases, efficient contact tracing, and the diagnosis of suspected SARS-CoV-2 infections. Our findings indicate that in respiratory samples, shedding endured for approximately 18-20 days, with the highest shedding levels occurring in the respiratory specimens of positive cases around 10 to 14 days after the onset of symptoms [29][30][31][32][33][34][35]. These insights have significant implications for public health strategies aimed at curbing the spread of the virus.…”
Section: Discussionmentioning
confidence: 73%
“…The availability of a highly sensitive and specific diagnostic assay is indispensable for the identification of cases, efficient contact tracing, and the diagnosis of suspected SARS-CoV-2 infections. Our findings indicate that in respiratory samples, shedding endured for approximately 18-20 days, with the highest shedding levels occurring in the respiratory specimens of positive cases around 10 to 14 days after the onset of symptoms [29][30][31][32][33][34][35]. These insights have significant implications for public health strategies aimed at curbing the spread of the virus.…”
Section: Discussionmentioning
confidence: 73%
“…All of the species involved in study, excluding M. mystacinus , have been prevoiusly identified as hosts for various coronaviruses. [ 21 , 22 ]…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 causes a wide range of wild and farm animals, humans as well as birds. An experimental study revealed a antiviral activity of Ivermectin against CoV virus.Genomic variants of this virus may cause future epidemic or pandemic due to the rapid evolution of corona viruses [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%